Determinants of adherence to micronutrient powder use among young children in Ethiopia. Issue 2 (9th November 2020) - Samuel, Aregash; Brouwer, Inge D.; Pamungkas, Nindya P.; Terra, Tosca; Lelisa, Azeb; Kebede, Amha; Osendarp, Saskia J. M.
Abstract: In Ethiopia, home fortification of complementary foods with micronutrient powders (MNPs) was introduced in 2015 as a new approach to improve micronutrient intakes. The objective of this study was to assess factors associated with intake adherence and drivers for correct MNP use over time to inform scale‐up of MNP interventions. Mixed methods including questionnaires, interviews and focus group discussions were used. Participants, 1, 185 children (6–11 months), received bimonthly 30 MNP sachets for 8 months, with instruction to consume 15 sachets/month, that is, a sachet every other day and maximum of one sachet per day. Adherence to distribution (if child receives ≥14 sachets/month) and adherence to instruction (if child receives exactly 15[±1] sachets/month) were assessed monthly by counting used sachets. Factors associated with adherence were examined using generalized estimating equations. Adherence fluctuated over time, an average of 58% adherence to distribution and 28% for adherence to instruction. Average MNP consumption was 79% out of the total sachets provided. Factors positively associated with adherence included ease of use (instruction), child liking MNP and support from community (distribution and instruction) and mother's age >25 years (distribution). Distance to health post, knowledge of correct use (OR = 0.74, 95% CI = 0.66–0.81), perceived negative effects (OR = 0.73, 95% CI = 0.54–0.99) and living in Southern Nations, Nationalities and People Region (OR = 0.59, 95% CI = 0.52–0.67) were inversely associated with adherence to distribution. Free MNP provision, trust in the government and field staff played a role in successful implementation. MNP is promising to be scaled‐up, by taking into account factors that positively and negatively determine adherence.